2022
DOI: 10.1038/s41467-022-34892-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of synthetic agonist activation of the nuclear receptor REV-ERB

Abstract: The nuclear receptor REV-ERB plays an important role in a range of physiological processes. REV-ERB behaves as a ligand-dependent transcriptional repressor and heme has been identified as a physiological agonist. Our current understanding of how ligands bind to and regulate transcriptional repression by REV-ERB is based on the structure of heme bound to REV-ERB. However, porphyrin (heme) analogues have been avoided as a source of synthetic agonists due to the wide range of heme binding proteins and potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…We therefore used a standard procedure of differentiating Thp-1 cells towards an inflammatory macrophage phenotype and evaluated the effects of our small molecule REV-ERB agonists on inflammatory mediators. Our results not only validated previously published results demonstrating the antiinflammatory effects of REV-ERB agonist SR9009, it also demonstrated that the new compound, STL-1267, has greater efficacy in these models as compared to SR9009 (Morioka et al, 2016;Morioka et al, 2021;Murray et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We therefore used a standard procedure of differentiating Thp-1 cells towards an inflammatory macrophage phenotype and evaluated the effects of our small molecule REV-ERB agonists on inflammatory mediators. Our results not only validated previously published results demonstrating the antiinflammatory effects of REV-ERB agonist SR9009, it also demonstrated that the new compound, STL-1267, has greater efficacy in these models as compared to SR9009 (Morioka et al, 2016;Morioka et al, 2021;Murray et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Measurments of footpad thickness show that a single administration of REV-ERB agonist (either SR9009 or STL1267) was sufficient to reduce footpad inflammation driven by λ-Carrageenan injection at 4-hpi (Figure 4B). STL1267 continued to suppress footpad inflammation at 24-hpi, suggesting that it may be more efficacious at the 50 mg/kg dose as compared to SR9009 which was given at 100 mg/kg, as determined by our previous work with these compounds (Solt et al, 2012;Murray et al, 2022). By 48-hpi, there was no significant change in footpad thickness as compared to the vehicle control group, which was expected given the rats only received a single dose of REV-ERB agonists and the compounds should have been completely metabolized by this time.…”
Section: A Single Dose Of Rev-erb Agonist Reduces Pain Behavior In Sp...mentioning
confidence: 86%
See 3 more Smart Citations